Review Study of Industrial Sociology (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Industrial sociology examines the relationship between work, industry, and society, focusing on how industrialization shapes social structures, labor relations, and organizational dynamics. This paper explores key concepts, theoretical perspectives, and empirical research in industrial sociology, highlighting the impact of industrial processes on workers, organizations, and broader societal changes.